# how does sum work?

1 view (last 30 days)
Pavel Kuzmitsky on 22 Nov 2020
Edited: Walter Roberson on 23 Nov 2020
I don't understand what I'm doing wrong, it should be -1, but it turns out -0.5
but if you calculate separately for s=0 and s=1 and add it up, it turns out that -1 is true
clear
clc
n=2;
m=0;
k=(n-m)/2;
q=(n+m)/2;
r2=0;
s=0:k;
R=sum((r2.^(n-(2.*(s)))).*...
(((-1).^(s)).*(factorial(n-(s))))/...
((factorial(s)).*(factorial(q-(s))).*(factorial(k-(s)))))
also, if you can explain how to improve the formula so that it can be used when
r2=linspace(0,1,500);
if you can, write comments on actions in the response so that it is clear how your code works

Walter Roberson on 23 Nov 2020
you have one / operator that should be ./

Pavel Kuzmitsky on 23 Nov 2020
I have summation should occur when changing s, r2 is an array, what operators are we talking about?
James Tursa on 23 Nov 2020
(((-1).^(s)).*(factorial(n-(s))))/... <-- that one
Walter Roberson on 23 Nov 2020
n = 6;
m=0;
k=(n-m)/2;
q=(n+m)/2;
r2 = linspace(0,1,25);
s = (0:k).';
R = sum((r2.^(n-(2.*(s)))) .* ...
(((-1).^(s)).*(factorial(n-(s)))) ./ ...
((factorial(s)).*(factorial(q-(s))).*(factorial(k-(s)))));
size(R)
ans = 1×2
1 25
plot(r2, R);
xlabel('r2'); ylabel('R');

R2020a

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!